(untitled) (Research, Society and Development, 2022)
The objective of this study was to review the literature on the identification of the impacts on the mental health of the elderly in the different aspects induced by the COVID-19 pandemic. Integrative literature review, performed through a search strategy in Latin American and Caribbean Literature in Health Sciences, Scopus and Web of Science, through the health descriptors "older adults", "mental health" and " COVID-19". We included 17 studies published from 2020 that addressed the repercussions of social isolation on the mental health of the elderly. Social isolation, the effect of the COVID-19 pandemic, was able to negatively affect the quality of life of the elderly, providing consequences on mental health conditions. Depressive and anxiety symptoms increased during the pandemic, reflecting in situations of stress, insomnia, fear and loneliness.